Early Byzantine metallurgical object at the site Gamzigrad - Romuliana in Eastern Serbia - Živić Maja (Journal of Mining and Metallurgy. Section B: Metallurgy)
The processing of waste powders from steel production in electric arc furnaces is a world problem. The presence of Fe, Zn, Cd, Pb, etc. in the powders makes them a valuable source for these metals. Zinc is the metal that is most often utilized, which leads to reduction of environmental pollution. The greatest problem in this connection is the presence of chlorine and fluorine in the powders, which influences the electroextraction of zinc in a significantly negative way. The presented paper shows the results from the study of the possibilities for zinc leaching from powders obtained in the steel production in Bulgaria. A detailed characterization of the powders was made using chemical analysis, XRD, DTA and TGA and Mössbauer spectroscopy. The results from the powder leaching with different solvents give the reason to recommend a technological scheme for the complete and total processing of the waste powders from steel production.